Stochastic impact assessment of PHEV charger levels in a microgrid - Singh A.; Maulik A.; Das D. (My University, 2025)
In this paper, we have investigated the impact of different plug-in hybrid electric vehicle (PHEV) charger topologies on the fuel cost, network loss, and loss allocation of a gridconnected AC microgrid. The presence of distributed generation, both renewable and non-renewable resources, has been considered in the problem formulation. Uncertainties related to PHEV load, electrical load, renewable generation, and grid power price have been modeled using 'Hong's 2m point estimate method'. The dispatchable units and the battery energy storage system are optimally scheduled to minimize the cost of operation. The network loss is allocated to different nodes using an exact loss allocation approach. Impacts of three charger types, namely-level 1, level 2, and level 3 on the system operating cost, loss, and loss allocation are investigated. Simulation results for a thirty-three node system are also presented. © 2021 IEEE.